Protective Effect of Celery ( Apium graveolens L. ) Essential Oil on the Experimental Model of Cuprizone-induced Multiple Sclerosis in Male C57BL/6 Mice - Tahoura Mohammadi-Ghohaki; Shahin Hassanpour; Morteza Zendedel kheybari (The Iranian Journal of Veterinary Science and Technology, 2023)
Considering the beneficial effects of Apium graveolens L. (Celery) on the nervous system, this study elucidates the protective effect of CEO on the experimental model of cuprizone-induced MS in male C57BL/6 mice. Frothy mice were allocated into four experimental groups: control, cuprizone (chew pellet containing 0.2 %CPZ), CEO (800 mg/kg), and CPZ+CEO. Animals received treatments based on their groups for 5 weeks. Finally, reflexive motor behavior and serum antioxidant levels were determined. Based on the findings, ambulation score, hind-limb suspension, front limb suspension, and grip strength significantly decreed in the mice treated with CPZ (p < 0.05). Hind limb foot angle, surface rights, and negative geotaxis significantly increased in the animals treated with CPZ (p < 0.05). Co-administration of CPZ+CEO significantly reduced the adverse effects of CPZ on ambulation score, surface righting, hind limb suspension, grip strength, and negative geotaxis (p < 0.05). Co-administration of CPZ+CEO significantly diminished the adverse effects of CPZ on the number of crosses in the open field test and duration on the rotarod (p < 0.05). Serum MDA activity increased while GPx, SOD, and TAS decreased in the mice treated with CPZ (p < 0.05). Co-administration of CPZ+CEO significantly reduced the adverse effects of CPZ on serum antioxidant levels (p < 0.05). These results suggested the protective effect of CEO against CPZ-induced MS mediated by its antioxidant activity.